PERBANDINGAN HASIL BELAJAR MATEMATIKA SISWA SULIT BELAJAR MELALUI PEMBELAJARAN TIPE SCRAMBLE MEDIA MANIPULATIF DENGAN MEDIA REALISTIK MENGGUNAKAN SINGLE SUBJEK RESEARCH PADA SISWA KELAS IV KECAMATAN TANETE RILAU - Syamsidar Majid; Rukli Rukli; Sulfasyah Sulfasyah (Jurnal Pendidikan dan Pengajaran Guru Sekolah Dasar (JPPGuseda), 2021)
COMPARISON OF MATHEMATICS LEARNING OUTCOMES OF STUDENTS WITH DIFFICULTY LEARNING THROUGH SCRAMBLE TYPE LEARNING MANIPULATIVE MEDIA WITH REALISTIC MEDIA USING SINGLE RESEARCH SUBJECTS FOR CLASS IV STUDENTS, TANETE RILAU DISTRICTThis type of research is Single Subject Research, so there is no direct control on the independent variables. The number of samples in this study is a single sample. The results showed that students' mathematics learning outcomes using manipulative media scramble type learning for class IV Tanete Rilau District described the fraction concept ability score in children using scramble learning with manipulative media in each phase and had changes, even the changes were reflected in each session. In the pre-intervention phase, the first session had a score of 51.5%, the second session 53.3%, and in the third session 62.9%. With a picture like that, the trend towards the graph shows an increase and is positive. The results of students' mathematics learning by using realistic media scramble type learning showed the score of fraction concept ability in children using scramble learning with manipulative media in each phase had changes, even the changes were reflected in each session. In the pre-intervention phase, the first session had a score of 72.3%, the second session 52.3%, and in the third session 64.9%. With such a picture, the trend towards the graph shows a downward trend. Student learning outcomes through the application of scramble-type learning using manipulative media and realistic media showed that the fraction concept ability test in scramble learning children with the help of appropriate media using realistic media overall level of scramble learning ability increased, especially when giving interventions using manipulative media and media. realistic and the results of the intervention showed a significant increase in the child's fraction concept ability. This is evidenced by the percentage score at baseline (A') which is higher than the percentage score for the intervention (B) and baseline (A).